Repeatability of the evaluation of systemic microvascular endothelial function using laser doppler perfusion monitoring: clinical and statistical implications - Tibiriçá, Eduardo (2011)
Universidade do Estado do Rio de Janeiro. Unidade de Diabetes. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Investigação Cardiovascular. Rio de Janeiro, RJ, Brasil.